Moving from silos to teamwork: integration of interprofessional trainees into a medical home model. Issue 5 (September 2014) - Long, Theodore; Dann, Sarah; Wolff, Marissa Lynn; Brienza, Rebecca S.
Abstract As the United States faces an impending shortage in the primary care workforce, interprofessional teamwork training to improve clinic efficiency and health outcomes is becoming increasingly important. Currently there is limited integration of interprofessional training in educational models for health professionals. The implementation of Patient Aligned Care Teams at the Department of Veterans Affairs (VA) has provided an opportunity for interprofessional collaboration among trainee and faculty providers within the VA system. However, integration of interprofessional education is also necessary to train future providers in order to provide effective team-based care. We describe a transportable educational model for health professional collaboration from our experience as a VA Center of Excellence in Primary Care Education, including a complementary novel one-year post-Master's adult nurse practitioner interprofessional clinical fellowship. With growing recognition that interprofessional care can improve efficiency and outcomes, there is an increasing need for programs that train future providers in collaboration and team-based care.